Considerations for a modern performance of John Field's Piano Sonata op. 1 no. 1 in E flat Major - Moynihan, Fionnuala (Royal Irish Academy of Music, 2016)
The wish to prepare John Field’s Piano Sonata op.1 no.1 in E flat major for a concert performance led the author to investigate and research the Urtext edition published by G. Henle Verlag (1983). As no autograph manuscript of Sonata op.1 no.1 is known to exist, this Urtext edition is based upon two early editions with annotations by the composer: the first edition published by Muzio Clementi in 1801 and an edition published in Berlin by Lischke in 1822. The editor of the Henle Urtext edition, Robin Langley, deemed the Lischke edition to be of greater importance as a primary source due to inconsistencies noted by him in the Clementi edition. All three editions were analysed and compared during the course of this investigative study. The author also studied the edition by Dittmar (1805-1808). The purpose of this dissertation is to create a performance of Sonata op.1 no.1 that is both guided and enlightened by thorough analysis of this work and an understanding of the environment surrounding its composition, performances, and subsequent republication during the composer’s lifetime. During the course of this study the development in piano construction during the period surrounding the publication of the two primary source manuscripts was traced and compared to the construction of a modern grand piano. The characteristics of pianistic techniques dating from the early nineteenth century were compared to those practised by modern pianists. A comparative study was carried out between the Clementi, Lischke and Henle editions with particular attention given to revisions made by the composer, discrepancies between the editions, fingering annotated by Field, articulation markings, dynamic markings and pedalling indications. The differences between pedalling styles from the early nineteenth century and those practiced by modern pianists were examined as was the presentation of pedal indications in printed scores. The origins of Field’s style of composition and pianism were explored with particular reference to, arguably, the two greatest influences in Field’s musical life: his teacher Muzio Clementi and one of the foremost pianist-composers of the period, Jan Ladislav Dussek. The obstacles faced by Langley during the course of the Henle Urtext edition’s production were investigated and the findings considered in relation to the author’s query as to whether the Henle Urtext edition is a bona fide Urtext or a valuable edition created by a well-educated and stylistically-aware editor.
Keywords: Music; Field, John, 1782-1837; Sonatas (Piano); Piano music; Field, John, 1782-1837. Sonata, piano, op 1 no 1, E flat major; Performance practice (Music)